ANALISIS KEKUATAN TARIK DAN KEKUATAN LULUH PELEBURAN ALUMINIUM PISTON BEKAS BERDASARKAN NILAI KEKERASANNYA UNTUK APLIKASI MATERIAL KAKI PALSU - Al Hassany, Ibnu Rosyid; Nurdin, Akhmad; Lutiyatmi, Lutiyatmi; Paundra, Fajar (Teknika, 2024)
The majority of prosthetic leg products currently circulating in Indonesia are imported and made from stainless steel. Even though it has several advantages, the price and production costs are relatively expensive. So, it is necessary to introduce other materials to make the prosthetic legs more affordable. One alternative material is aluminum. Aluminum material can be fulfilled by recycling used aluminum. This research conducted a study on the tensile strength and yield strength of remelting used aluminum pistons based on the hardness value. The research material is aluminum from used pistons from large vehicles (buses or trucks) mixed with 20% silicon aluminum. Specimens with a target silicon (Si) content of 12%, 14%, and 16% were cast using a sand mold using the closed mold casting method. The Brinell hardness test refers to ASTM E10-15. The reference for the feasibility of melting as an alternative material is that its yield strength must be greater than the maximum stress on the prosthetic leg, which is 153 N/mm2. The average hardness for the Si 12%, Si 14%, and Si 16% samples is 87.35 HB, 101.01 HB, and 112.03 HB, respectively. The tensile strength for the Si 12%, Si 14%, and Si 16% samples is 125.30 N/mm2, 175.33 N/mm2, and 215.44 N/mm2. The yield strength of the Si 12%, Si 14%, and 16% samples is 80.02 N/mm2, 112.75 N/mm2, and 138.47 N/mm2. The melting results for the three samples cannot yet be applied to prosthetic limb materials because the yield strength is lower than the maximum stress that occurs.